2022
DOI: 10.29040/jiei.v8i3.6501
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Dana ZIS (Zakat, Infak, Sedekah), Pertumbuhan Ekonomi, Angka Harapan Hidup, Rata-Rata Lama Sekolah, Dan Pengeluaran Perkapita Terhadap Tingkat Kemiskinan Di Indonesia Periode 2010-2021

Ismi Wulandari,
Abdul Aziz Nugraha Pratama

Abstract: This study was conducted to find out how the influence of ZIS, economic growth, life expectancy, average length of schooling, and per capita expenditure on poverty levels in Indonesia for the period 2010-2021. This study uses secondary data in the form of time series. The data collection method was carried out by taking data from the documentation of the relevant institutions, namely the Indonesian Central Statistics Agency (BPS) and BAZNAS. The data obtained were then processed using the tools of eviews 10. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
2
5
0
1
Order By: Relevance
“…This research supports research from (Wulandari & Pratama, 2022) that the presence of ZIS will affect a country's economic growth (Badriyah & Munandar, 2021) and that the distribution of ZIS funds has a positive and significant effect on economic growth in Indonesia (Anggraini et al, 2018) which obtained the result that zakat, infaq, and alms had a positive and significant effect on economic growth in Indonesia. This was due to the ZIS receipts from mustahik, which could be used as capital to open business opportunities that would later create new jobs.…”
Section: Effect Of Zis Acceptance On Economic Growth In Indonesiasupporting
confidence: 85%
“…This research supports research from (Wulandari & Pratama, 2022) that the presence of ZIS will affect a country's economic growth (Badriyah & Munandar, 2021) and that the distribution of ZIS funds has a positive and significant effect on economic growth in Indonesia (Anggraini et al, 2018) which obtained the result that zakat, infaq, and alms had a positive and significant effect on economic growth in Indonesia. This was due to the ZIS receipts from mustahik, which could be used as capital to open business opportunities that would later create new jobs.…”
Section: Effect Of Zis Acceptance On Economic Growth In Indonesiasupporting
confidence: 85%
“…The same research was conducted by Wulandari et al (2022) during the period of 2010-2021, showing that life expectancy has a negative and significant impact on the poverty rate in Indonesia. This means that the higher the life expectancy, the lower the poverty rate, and vice versa.…”
Section: The Influence Of Life Expectancy On Povertymentioning
confidence: 76%
“…Study conducted by Wulandari et al (2022) found that life expectancy has a significant negative impact on the poverty rate in Indonesia during the period 2010-2021. This means that the higher the life expectancy, the lower the poverty rate, and vice versa.…”
Section: Figure 2 Populationmentioning
confidence: 99%
“…AHH yang tinggi dapat merefleksikan adanya usaha dalam memperbaiki status kesehatan masyarakat yang dapat berdampak dalam pengurangan tingkat kemiskinan (Ginting, 2020). Wulandari & Pratama (2022) pun menyebutkan bahwa terdapat pengaruh negatif yang signifikan dari AHH terhadap kemiskinan di Indonesia pada periode 2010-2021.…”
Section: Angka Harapan Hidup (Tahun) Dan Persentase Kemiskinanunclassified